2008
DOI: 10.1111/j.1529-8817.2007.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSING PHYLOGENETIC AFFINITIES AND SPECIES DELIMITATIONS IN KLEBSORMIDIALES (STREPTOPHYTA): NUCLEAR‐ENCODED rDNA PHYLOGENIES AND ITS SECONDARY STRUCTURE MODELS IN KLEBSORMIDIUM, HORMIDIELLA, AND ENTRANSIA1

Abstract: Nuclear‐encoded SSU, group I intron, and internal transcribed spacer (ITS) rDNA sequences were obtained for 16 strains of green algae representing species of Klebsormidium, Hormidiella attenuata, and Entransia fimbriata (for taxonomic authorities, see Table S1 in the supplementary material). The SSU phylogeny resolved a well‐supported clade Klebsormidiales in the Streptophyta that comprised authentic Klebsormidium isolates described recently in a monograph by G. M. Lokhorst and various strains from culture col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 50 publications
8
49
1
2
Order By: Relevance
“…Even if purely morphological data are sufficient for standard ecological studies (where comparison of individual morphotypes illustrates influences of investigated factors), accurate description of the algal flora is essential for potential future comparisons. Since the recent molecular studies have shown a high hidden diversity of aero-terrestrial algae with little morphological differentiation (huss et al 1999, kRienitz et al 2004, sLuiman et al 2008, I place emphasis on a detailed morphological description of the investigated species. Hence, the majority of the investigated species are illustrated .…”
Section: Species Composition and Diversitymentioning
confidence: 99%
“…Even if purely morphological data are sufficient for standard ecological studies (where comparison of individual morphotypes illustrates influences of investigated factors), accurate description of the algal flora is essential for potential future comparisons. Since the recent molecular studies have shown a high hidden diversity of aero-terrestrial algae with little morphological differentiation (huss et al 1999, kRienitz et al 2004, sLuiman et al 2008, I place emphasis on a detailed morphological description of the investigated species. Hence, the majority of the investigated species are illustrated .…”
Section: Species Composition and Diversitymentioning
confidence: 99%
“…4). The Klebsormidiophyceae includes the freshwater or terrestrial genera Klebsormidium, Interfilum and Entransia, which form unbranched filaments or sarcinoid packets that produce asexual motile spores with streptophyte characteristics (Cook, 2004b;Sluiman et al, 2008). Diversity and phylogenetic relationships within the Klebsormidiophyceae have been studied by Rindi et al (2008;2011) and Mikhailyuk et al (2008).…”
Section: The Early Diverging Charophytesmentioning
confidence: 99%
“…has a convoluted nomenclatural history dating back to the 1800s (reviewed by Lokhorst 1996; see also Novis 2006;Sluiman et al 2008). Briefly, the basionym for the type species of the genus Á K. flaccidum (Ku¨tz.)…”
Section: Introductionmentioning
confidence: 99%